2023
DOI: 10.47080/jeltl.v6i1.2477
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension Difficulties in Indonesian Efl Students

Abstract: Getting knowledge by reading is one of the prominent ways, and reading comprehension is a skill to help students in learning process. In fact, there are many EFL students have some difficulties in reading comprehension. The objective of this study is to analyze the students’ difficulties in reading comprehension skills. Descriptive qualitative method is used in this study, and by using purposive sampling, 98 students of Basic Reading Class at English Education Program in University of Indraprasta PGRI were eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Moreover, figure 8 revealed that the participants also stated that the significance factors that cause them to have a hard time in understanding listening comprehension in an English test were the speed of the speaker (66.7%), vocabulary (27.3%), the accent of the speaker (18.2%), and the topic of the conversation (15.2%). It is also correlated with Ramadhianti & Somba (2021) their research revealed that 64.7% students in the research found it difficult to understand the subject matter in the audio and 98.8% students stated that the speaker talked too fast and they could not catch up with the pace of the speaker whilst listening to the audio to comprehend its meaning. On top of that, Kurtuldu & Ozkan's (2022) participants in their research stated that topic was also their issue in being unable to ------------------------------------------------------------------------------------------------------------------ understand the speaker within the audio in listening comprehension.…”
Section: Maharani (2023)mentioning
confidence: 73%
“…Moreover, figure 8 revealed that the participants also stated that the significance factors that cause them to have a hard time in understanding listening comprehension in an English test were the speed of the speaker (66.7%), vocabulary (27.3%), the accent of the speaker (18.2%), and the topic of the conversation (15.2%). It is also correlated with Ramadhianti & Somba (2021) their research revealed that 64.7% students in the research found it difficult to understand the subject matter in the audio and 98.8% students stated that the speaker talked too fast and they could not catch up with the pace of the speaker whilst listening to the audio to comprehend its meaning. On top of that, Kurtuldu & Ozkan's (2022) participants in their research stated that topic was also their issue in being unable to ------------------------------------------------------------------------------------------------------------------ understand the speaker within the audio in listening comprehension.…”
Section: Maharani (2023)mentioning
confidence: 73%
“…Secondly, listeners' poor comprehension is caused by these factors such as: mispronounced words by speaker, tedious topic, tiresomeness, lacking of prior knowledge about topic, first exposure to target language, predicting what may come next, and stream of speech. These findings may be buttressed with these studies (Derakhshan, Kruk, Mehdizadeh, & Pawlak, 2021;Jyoti, 2020;Ramadhianti, & Somba, 2021;Sabih-Ul-Hassan, Gul, & Imran, 2023;Saipullah, Syahri, & Susanti, 2021;Winn, & Teece, 2021). Having this in view, it is the responsibility of the speaker to ensure words uttered clearly; to ensure the topic is interesting or adding something new in the knowledge of the listener; and to ensure communication should be in moderate form.…”
Section: Discussionmentioning
confidence: 95%
“…Thirdly, listening problems related to the speaker show that the listener counter problems due to these issues: natural speech full of pauses, hesitation, and hedges; mispronounced words and phrases; fast pace of speech; using a variety of accents; and lacking long enough pause while communication. Similarly, various studies (e.g., Ekayati, 2020;Gilakjani, & Sabouri, 2016;Ramadhianti, & Somba, 2021;Richards, Hohl, Whiteside, Ludman, Grossman, Simon, & Williams, 2019) have accorded that the pace of communication becomes a challenge for a listener to digest message since speedy conversation makes many things unclear. Although effective talk is possible when a conversation takes place in a natural tone with reasonable pauses.…”
Section: Discussionmentioning
confidence: 99%
“…The participants of their research acknowledged that prior knowledge influenced their reading comprehension. In a similar vein, Ramadhianti and Somba (2023) discovered that providing students with diverse text, particularly different from students' culture, created a challenge for them as students did not possess adequate prior knowledge. Riadil (2020) also found that students encountered challenges when reading text different from their culture.…”
Section: Efl Learners' Reading Difficultiesmentioning
confidence: 99%